A retrospective study to assess prevalence of gestational diabetes mellitus among those who delivered in Saveetha Medical College and Hospital - Gopalan, Sharmila Kumar; Kalimuthu, Kohila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational diabetes mellitus (GDM) defined as any degree of carbohydrate intolerance with onset or first recognition during pregnancy contributes to about 90% of diabetes complicating pregnancy. GDM imposes risks for both mother and fetus, some of which continues throughout the life of mother and child. The objective of the present study was to determine the prevalence of gestational diabetes mellitus and the associated risk factors among those who delivered in Saveetha medical college and hospital. Methods: A retrospective study was conducted by analysing the medical records of the patients who were admitted in the Department of Obstetrics and Gynaecology over a period of 1 year at Saveetha medical college and hospital, Chennai, Tamil Nadu, India. The diagnosis of GDM was made mainly by 75gm one step oral glucose tolerance test (OGTT). The guideline endorses 2-hours 75-gm OGTT, irrespective of last meal timings with a cut off value of ≥140 mg/dl. All data was analysed by simple descriptive statistics and percentage method. Results: In the present study, the total number of deliveries for 1 year from April 2018 - March 2019 were 511 and among those the total number of antenatal mothers with GDM who delivered were 46. Therefore the prevalence of GDM was calculated to be 9% or 90 per thousand deliveries. In the present study, 37 (65.1%) pregnant women of GDM group were seen in the age group of above 25 years, 27 (58.59%) were multiparous, 25(54.25%) pregnant females with GDM were found to have overweight and obese out of 46 cases. Conclusions: Our current study concludes the Prevalence of GDM in Saveetha Medical College Hospital is 9% between April 2018-March 2019. We have identified the following risk factors for developing GDM: multiparity≥2; previous history of diabetes mellitus; age ≥ 25; BMI ≥25; and family history of diabetes.